Chemical and electrochemical water oxidation catalyzed by heteroleptic Ru(III) complexes of anionic 2, 6 pyridine dicarboxylate ligand: Experimental and theoretical study. (1st August 2022) - Khan, Sahanwaj; Naskar, Subhendu
Graphical abstract: Two new Ru III complexes with anionic N, O donor pyridine dicarboxylate (pdc 2− ) ligand along with neutral bipyridine moieties have been found to effectively catalyze the water oxidation both chemically using Cerric ammonium nitrate (CAN) and electrochemically. Spectro-chemical and electrochemical study and theoretical evidences by means of DFT calculation support the I2M mechanism to be followed by the molecules to peruse the water oxidation reaction in the current study. Abstract: Herein we report two new mononuclear heteroleptic Ruthenium complexes, 1 and 2 with anionic N, O donor pyridine dicarboxylate (pdc 2- ) ligand along with neutral bipyridine moieties. The general formula of the complexes are [Ru III (pdc 2- )(L1 )Cl] (1), [Ru III (pdc 2- )(L2 )Cl] (2) (Where L1 = bipyridine, L2 = 4, 4′-dimethylbipyridine). Synthesis, characterization and water oxidation catalytic properties of both complexes were investigated. A combined theoretical (DFT) and experimental study were carried out to investigate the catalytic (in presence of CAN) and electrocatalytic activity of 1 and 2 for water oxidation in aqueous solution at pH ∼ 1. During electrocatalysis, the catalytic activity wave has been detected in acetonitrile/water 1:9 (v/v) solution in the range 1.39–1.41 V vs SCE. pH based electrochemistry reveals that, water oxidation (at pH = 1) takes place via sequential proton-electron transfer process to form a Ru V = O moiety, which oxidises water through I2M pathway. For water oxidation by CAN, both the molecules show appreciably high TOF values 3.47971 x10-4 s −1 and 1.183 × 10–3 s −1 for 1 and 2 respectively in comparison to similar molecules [1, 2].